Firm Performance, Institutional Ownership and Capital Structure: A Case of Malaysia. (25th November 2015) - Pirzada, Kashan; Mustapha, Mohd Zulkhairi Bin; Wickramasinghe, Danture
Abstract: The paper aims to examine the significant relationship amongst institutional stockholdings and firms' performance as measured by ROA, ROE, PE, EPS and capital structure as measured by long term debt to capital ratio of companies listed on the Main Board of Bursa Malaysia. The results show that there is a significant relationship between the institutional stockholdings on the firms' performance measured by EPS and PE ratio of firms listed on the Main Board of BURSA. Moreover, it is revealed that there is no significant relationship between the institutional stockholdings on firms' capital structure.